Weapons of the Rich: Strategic Behavior and Collective Action of Private Entrepreneurs in China. (September 2019) - Heberer, Thomas; Schubert, Gunter
This article, the product of several years of extensive fieldwork, seeks to reinvigorate the debate on China's private entrepreneurs by arguing that they have become a "strategic group" within the Chinese polity. While they do not openly challenge the current regime, they continuously alter the power balance within the current regime coalition, which connects them to the party-state at all administrative levels. As the future of Chinese socialism depends on the sound development of the private-sector economy and, therefore, on the promotion of private entrepreneurship, it can be expected that entrepreneurial influence within the regime coalition will rise, with inevitable consequences for regime legitimacy and stability.